2021
DOI: 10.4093/dmj.2020.0277
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Derived Myosteatosis and Metabolic Disorders

Abstract: The role of ectopic adipose tissue infiltration into skeletal muscle (i.e., myosteatosis) for metabolic disorders has received considerable and increasing attention in the last 10 years. The purpose of this review was to evaluate and summarize existing studies focusing on computed tomography (CT)-derived measures of myosteatosis and metabolic disorders. There is consistent evidence that CT-derived myosteatosis contributes to dysglycemia, insulin resistance, type 2 diabetes mellitus, and inflammation, and, to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 58 publications
0
45
0
Order By: Relevance
“…A longitudinal study suggested that increase in intermuscular adipose was a more consistent marker of aging than sarcopenia ( 23 ). Myosteatosis is also closely related to insulin resistance and has been reported as an independent risk factor of diabetes ( 19 ). It is indicated that the intramyocellular lipids content, which is analyzed by muscle biopsies, was significantly correlate with insulin resistance in T2DM patients, obesity as well as lean subjects ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study suggested that increase in intermuscular adipose was a more consistent marker of aging than sarcopenia ( 23 ). Myosteatosis is also closely related to insulin resistance and has been reported as an independent risk factor of diabetes ( 19 ). It is indicated that the intramyocellular lipids content, which is analyzed by muscle biopsies, was significantly correlate with insulin resistance in T2DM patients, obesity as well as lean subjects ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A high muscle fat content (often known as myosteatosis) may play a key role in the risk of metabolic abnormalities. Studies have indicated that myosteatosis is associated with insulin resistance, type 2 diabetes mellitus (T2DM), dyslipidemia and cardiometabolic diseases ( 17 , 18 ), and there was also a link between skeletal muscle density and biomarkers of inflammation, such as CRP, IL-6, TNF-α, adiponectin and leptin ( 19 ). Myosteatosis has also been identified as a risk factor for decreased muscle strength, osteoporotic fractures, and reduced physical function ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Computerized tomography scan data show myosteatosis has been associated with low muscle strength, poor preoperative physical fitness, muscle metabolic dysfunction, and mortality in different populations [110,132,133]. Myosteatosis has also been associated with greater risk of prediabetes and type 2 diabetes, increased homeostasis model assessment for insulin resistance (HOMA-IR), as well as circulating levels of glucose, insulin, CRP, and IL-6 [134]. Also importantly, patients with both myosteatosis and low muscle mass may present at greater risk for poorer outcomes, compared to each of these conditions alone [30,135].…”
Section: Computerized Tomography Imagingmentioning
confidence: 99%
“…It is defined as a muscle mass two standard deviations below the healthy young adult mean [25]. Myosteatosis is a fat infiltration of the skeletal muscle mass with an increased proportion of intramuscular and intermuscular fat that could impact muscle function and lead to a systemic inflammation [26].…”
Section: Muscle Alterations and Hepatic Encephalopathy In Liver Cirrh...mentioning
confidence: 99%
“…Regarding myosteatosis, the physiopathological association with hyperammonemia and HE is more complex and partially unknown. Myosteatosis seems to derive from a complex mechanism involving the metabolism of fatty acids and glycogen; the pivotal point of this process is mediated by the proinflammatory state that is present and that leads to muscle depletion [26]. Nardelli et al have demonstrated the association between myosteatosis and HE, hypothezing that fat infiltration, by reducing the fat-free mass, may contribute to the reduction of leads to partial loss of function of glutamate synthetase, expressed in the muscle cell.…”
Section: Liver-muscle Axis and Hyperammonemia: A Link To Explorementioning
confidence: 99%